Analysis of the Comfort Level of Climate in the Padang Coastal Tourism Area Using the Holiday Climate Index (HCI) Method - Randy; Nofi Yendri Sudiar; Ahmad Fauzi; Letmi Dwiridal (Universitas Negeri Padang, 2023)
Padang city is one of the regions of Indonesia that has potential in the tourism sector, one of which is beach tourism. The tourism sector is one of the largest sectors and the main mainstay for the economy in various countries, including Indonesia. Countries that rely on the tourism sector must pay attention to several factors that attract tourists, one of which is climate comfort. Climate information is a major factor in choosing a tourist trip. This study aims to analyze the level of climate comfort in the coastal tourism area of Padang City using the Holiday Climate Index (HCI) method. HCI uses climate parameters such as air temperature, humidity, wind speed, rainfall, and cloud cover. HCI calculation data in the form of observation data obtained from the Meteorology Climatology Geophysics Agency (BMKG) station at Minangkabau International Airport and the Teluk Bayur Maritime Meteorology Station from 2011-2020, direct measurement data from August to September, and questionnaires. The results of the HCI analysis show that the city of Padang is comfortable throughout the year, with the HCI value in the range of 58.6-71.6 which is categorized as acceptable to very good. The results obtained through direct measurements also obtained comfortable results throughout the day with HCI values in the range of 70-80. Perceptions of tourists interviewed also stated that overall tourists felt comfortable with the percentage of respondents as much as 74.1%. HCI can be used as a source of information to determine the value of climate comfort in tourist areas.